GREEN SYNTHESIS AND CHARACTERIZATION OF SILVER NANOPARTICLE USING LEAF EXTRACT OF CAPPARIS ZEYLANICA - K. SARANYAADEVI; V. SUBHA; R. S. ERNEST RAVINDRAN; RENGANATHAN, SAHADEVAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The green synthesis of Silver nanoparticles (AgNPs) using the aqueous extract of Capparis Zeylanica plant leaves act as a reducing and capping agent has been reported in the present work. The formation of silver nanoparticles was observed by the change of colour from colourless to dark brown by the addition the leaf extract. Nanoparticles were characterized with the help of UV-Vis absorption spectroscopy analysis, Fourier Transform Infrared (FTIR) analysis, X-ray diffraction analysis (XRD), Scanning Electron Microscopy (SEM) & EDX analysis, and Transmission Electron Microscopy (TEM) analysis. The prepared AgNPs were monodispersed, spherical in shape with the particle size in a range of 50-90 nm.